Pelvic floor exercises - a clinical study - Pal, Manidip (Asian Journal of Medical Sciences, 2014)
Objective: To assess the effectiveness of pelvic floor exercise. Materials and methods: Hundred (100) patients of pelvic organ prolapse (POP), stress urinary incontinence (SUI) and overactive bladder (OAB) were included. They were advised pelvic floor exercise in stepwise incremental manner. Each time exercise comprised of 10 seconds holding up and 10 seconds relaxation. To start with it was 5 times each in the morning, noon, evening and night; making it 20 times per day. Every week 5 times increment. So by 5th week it was 25 times each in the morning, noon, evening and night; making it 100 times per day. After 6 months patients were assessed by their subjective feeling of improvement and clinical assessment. Results: After 6 months of therapy patients subjective feeling of improvement for POP, SUI and OAB were 73%, 84.1%, 58.3% respectively; though objective assessment did not show this much improvement. Conclusion: Pelvic floor exercise is an easy, effective and non-invasive tool that can be considered as first line therapy for these patients. Asian Journal of Medical Science, Volume-5(3) 2014: 95-98 http://dx.doi.org/10.3126/ajms.v5i3.9113